PENGARUH GREEN PRODUCT DAN GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK ELEKTRONIK MERK SHARP DI ELECTRONIC CITY CIPINANG INDAH MALL JAKARTA TIMUR - Widodo, Sri (Feb Universitas Dirgantara Marsekal Suryadarma, 2020)
This study aims to determine: 1) The effect of green products on purchasing decisions for Sharp brandelectronic products at Electronic City Cipinang Indah Mall, East Jakarta; 2) The effect of green marketingon purchasing decisions for Sharp brand electronic products at Electronic City Cipinang Indah Mall, EastJakarta; 3) Simultaneously the effect of green product and green marketing on the Purchase Decision ofSharp brand electronic products at Electronic City Cipinang Indah Mall, East Jakarta. This study uses aquantitative approach. The research instrument was in the form of a questionnaire. The sample usedamounted to 66 respondents namely consumers of Sharp brand electronic products at Electronic CityCipinang Indah Mall, East Jakarta. Test the validity of the instrument using the Pearson Product Moment correlation formula. Reliability test using Alpha Cronbach. Hypothesis testing uses multiple regressionanalysis.Keywords: green product, green marketing, purchasing decision.